Heavy Menstrual Bleeding-Visual Analog Scale, an Easy-to-Use Tool for Excessive Menstrual Blood Loss That Interferes with Quality-of-Life Screening in Clinical Practice - Josep Perell?; Pau Pujol; Montse P?rez; Maite Art?s; Joaquim Calaf (Mary Ann Liebert, 2022)
Background: Heavy menstrual bleeding (HMB) is defined as excessive menstrual blood loss that interferes with quality of life (QoL). The methods for assessing HMB are not suited for clinical practice. We analyzed the validity of a combined visual analog scale (VAS) tool assessing the intensity of menstrual bleeding (VASInt) and its impact on activities of daily living (VASImp) to identify women with HMB. Materials and Methods: Analysis conducted in the data set used to validate the Spanish HMB screening tool SAMANTA questionnaire. A logistic regression analysis was used to construct the model. Reference standard was the pictorial blood loss assessment chart (PBAC). The performance of the HMB-VAS and the SAMANTA questionnaire was compared. Correlation with SAMANTA questionnaire, PBAC, and other QoL measurements was assessed. Results: The resulting function (HMB-VAS score?=?10.86???VASInt score +2.48???VASImp score) showed a slightly lower accuracy versus the SAMANTA questionnaire (86.8% vs. 87.9%) but a similar area under the curve: 0.9396 versus 0.943, respectively (p?=?0.6605). The cutoff point was established as 700. After rounding the regression coefficients, the resulting function (11???VASInt +2???VASImp) showed 87.6% accuracy. The correlation of HMB-VAS with the SAMANTA questionnaire was strong (r: 0.79819; p?<?0.0001), whereas the correlation was moderate to strong with the PBAC (0.59299; p?<?0.0001) and weak with the QoL (EuroQoL five dimensions five levels questionnaire [EQ-5D-5L]) and well-being (Psychological General Well-Being Index [PGWBI]) scales (EQ-5D-5L VAS and Index: ?0.20332 and ?0.24384; PGWBI: ?0.21680; p?<?0.0001 for both). Conclusion: The HMB-VAS shows good performance for HMB screening, providing an easy-to-use alternative to other psychometric tools.